RESTORATIVE JUSTICE HAKIM TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DI PENGADILAN NEGERI LHOKSEUMAWE - Sumiadi Sumiadi; Laila M Rasyid; Romi Asmara (Fakultas Hukum Universitas Gadjah Mada, 2017)
Children are part of the younger generation as one of the human resources as potential successors inthe future. Violation of law that occurs in the community not only done by adults but also by children,the implementation of the sentence would have been very different from adults. In children should morebe rehabilitation rather than punitive. The results showed that judge who examine and rule on cases ofchildren in conflict with the law in District Court Lhokseumawe still think positivistic/legalistic wheredecisions are decided by the judges commonly used approach based on the criminal justice system.